Application of a Diagnostic Clinical Model for the Management of Hospitalized Patients with Suspected Deep-vein Thrombosis - Wells, Philip S.; Anderson, David R.; Bormanis, Janis; Guy, Fred; Mitchell, Michael; Gray, Lisa; Clement, Cathy; Robinson, K. Susan; Lewandowski, Bernard (Thrombosis and Haemostasis, 1999)
The purpose of this study was to evaluate whether the determination of pretest probability using a simple clinical model and the SimpliRED D-dimer could be used to improve the management of hospitalized patients with suspected deep-vein thrombosis. Consecutive hospitalized patients with suspected deep-vein thrombosis, had their pretest probability determined using a clinical model and had a SimpliRED D-dimer assay. Patients at low pretest probability underwent a single ultrasound test. A negative ultrasound excluded the diagnosis of deep-vein thrombosis whereas a positive ultrasound was confirmed by venography. Patients at moderate pretest probability with a positive ultrasound were treated for deep-vein thrombosis whereas patients with an initial negative ultrasound underwent a single follow-up ultrasound one week later. Patients at high pretest probability with a positive ultrasound were treated whereas those with negative ultrasound underwent venography. All patients were followed for three months for the development of venous thromboembolic complications. Overall, 28% (42/150), and 10% (5/50), 21% (14/71) and 76% (22/29) of the low, moderate and high pretest probability patients, respectively, had deep vein thrombosis. Two of 111 (1.8%; 95% CI = 0.02% to 6.4%) patients considered to have deep vein thrombosis excluded had events during three-month follow-up. Overall 13 of 150 (8.7%) required venography and serial testing was limited to 58 of 150 (38.7%) patients. The negative predictive value of the SimpliRED D-dimer in patients with low pretest probability was 96.2%, which is not statistically different from the negative predictive value of a negative ultrasound result in low pretest probability patients (97.8%). Management of hospitalized patients with suspected deep-vein thrombosis based on clinical probability and ultrasound of the proximal deep veins is safe and feasible.Dr. Philip Wells and Dr. David Anderson are the recipients of Research Scholarships from the Heart and Stroke Foundation of Canada.